THE PREVALENCE OF PERIODONTAL TISSUE DISEASES IN YOUNG INDIVIDUALS ON THE BACKGROUND OF CROWDED TEETH - A.V. Mandych (Український стоматологічний альманах, 2018)
The abnormalities of maxillodental system take one of the leading places among diseases of the maxillofacial area. Thus, they are diagnosed more than in 50% cases among the younger population and in 30% cases among the adult population.